PENGARUH METODE BRAINSTORMING KOLABORASI DENGAN MEDIA VISUAL TERHADAP KETERAMPILAN BERBICARA SISWA KELAS IV SDN 8 PRAYA - Liza Suditasari; Ida Bagus Kade Gunayasa; Heri Hadi Saputra; Heri Setiawan (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2021)
This study aims to determine the effect of the visual media-assisted brainstorming method on the speaking skills of fourth graders at SDN 8 Praya in the 2018/2019 academic year. This type of research is an experimental study with a Quasi Experimental Design type of Nonequivalent Control Group Design. The population in this study amounted to 46 students. The data collection technique used is saturated sampling with a sample of 46 students. Data collection techniques in this study used documentation, test results of students' speaking skills and teacher teaching observation sheets. The data obtained were tested using the t-test (t-polled variance). Based on the post-test results, it was obtained that the average value of students' speaking skills in the experimental class was 77.10 while in the control class was 74.77. The results of hypothesis testing obtained results of 0.0233 and 2.0186 at a significance level of 5%, so that it can be seen that tcount ttable. In accordance with the test criteria, it shows that Ho is accepted and Ha is rejected. So it can be concluded that there is no significant effect in the application of the visual media-assisted brainstorming method on the speaking skills of fourth graders at SDN 8 Praya in the 2018/2019 academic year.